Konfrontasi Amerika Serikat dan Iran dalam Joint Comprehensive Plan of Action (JCPOA) - Satwika Paramasatya; Sigit Wiranto (Universitas Airlangga, 2019)
Iran Nuclear Agreement or Joint Comprehensive Plan of Action (JCPOA)was the result of diplomatic negotiations achieved by the United States,United Kingdom, France, Russia, China, Germany, and Iran in 2015. Thenewly elected president of the United States Donald Trump brought newpolicies to the Iran’s nuclear issue. On May 8, 2018 The US governmentunilaterally withdraw themselves from the JCPOA agreement anddecided to reimpose the sanctions for Iran. This research tries to analyzewhy the US changed its policy to withdraw from the nuclear agreement byusing analytic eclecticism, with the combination of the security dilemmaand cognitive consistency theory. The result of this research shows thatthe US’ withdrawal from JCPOA psychologically caused by Trump’scognitive consistency. He thought that Iran’s nuclear agreement is a badand unreliable agreement because under this nuclear agreement, US andits allies still feel the security dilemma. Therefore, it pushed Trump toincrease the pressure to Iran by withdrawing themselves from the nuclearagreement.